(untitled) (Annual of the Faculty of Philosophy in Skopje, 2012)
As can be seen, the competing discourses for and against humanitarian intervention reflect different assumptions about the relationship between order and justice. Proponents of humanitarian intervention emphasise that justice is a prerequisite for long term order on the state level as well as on the international level. Critics of humanitarian intervention maintain that order is a precondition for justice and that humanitarian interevention - especially in the absence of concensus among the great powers - might endanger order and thereby undermine the precondition for justice on both the international level and within weak states. In sum, the different approaches to the relationship between order and justice produce indeterminate conclusions about the political and moral dilemas involved in humanitarian intervention. The relationship between order and justice is immensely complicated and precludes any possibility of an absolute and principled etic of intervention (or of non-intervention, for that matter) which stands on solid ground. This indeterminacy is likely to act as a constraint on governments contemplating humanitarian intervention. What the most responsible choise would be in any particular situation will depend on the concrete circumstances of the case, on instrumental considerations, and on a complex balancing act between considerations of order and considerations of justice on different levels and over various time lines. In the last instance, it depends on defenitions of national interest. Moreover, a significant part of the evaluations of a specific case relates to the questions whether an action would be lawful or not and what would be the long term effects of an act on the development of internatioanal law and its standing.